2016
DOI: 10.18203/issn.2454-5929.ijohns20160064
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillostyloidectomy for Eagle’s syndrome: a study of 20 cases

Abstract: <p class="abstract"><strong>Background:</strong> Eagle’s syndrome is a pain syndrome which occurs due to elongated and misdirected styloid process. It is commoner than generally thought.</p><p class="abstract"><strong>Methods:</strong> 20 cases of styalgia were diagnosed and prospectively studied at two hospitals. The characteristic symptoms were chronic throat pain and foreign body sensation in throat. Diagnosis was made with clinical symptoms, physical examination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Singh et al have shown in their study that 60% of their study population who had elongated styloid process presented with chronic tonsillitis. 4 Naik et al observed in their study that elongated styloid process and chronic tonsillitis were co-existent in all their cases. 5 In our study out of 160 chronic tonsillitis patients 119 had elongated styloid process which accounts to 73.4%.…”
Section: Discussionmentioning
confidence: 91%
“…Singh et al have shown in their study that 60% of their study population who had elongated styloid process presented with chronic tonsillitis. 4 Naik et al observed in their study that elongated styloid process and chronic tonsillitis were co-existent in all their cases. 5 In our study out of 160 chronic tonsillitis patients 119 had elongated styloid process which accounts to 73.4%.…”
Section: Discussionmentioning
confidence: 91%
“…Eagle syndrome as first described by Watt Eagle in 1937 is a pain syndrome due to local neurovascular impinging caused by a styloid process elongation 1. The incidence of elongated styloid process can be up to 7%, but only a small percentage of this group (5%–10%) is symptomatic 2 3. Most patients will have the classic syndrome of neck pain and dysphagia, caused by compression on the glossopharyngeal nerve, and only a few patients will have carotid artery involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The classic form of presentation, also known as stylohyoid syndrome, is caused by compression of cranial nerves V, VII, IX, X and their branches coursing through parapharyngeal space, and results in pain in the anterolateral neck with referred pain to the ear, foreign body sensation in the throat and dysphagia 1–3. Pain can be triggered by chewing, swallowing or turning of the head.…”
Section: Introductionmentioning
confidence: 99%